2020
DOI: 10.1016/j.redox.2020.101781
|View full text |Cite
|
Sign up to set email alerts
|

Complement activation, lipid metabolism, and mitochondrial injury: Converging pathways in age-related macular degeneration

Abstract: The retinal pigment epithelium (RPE) is the primary site of injury in non-neovascular age-related macular degeneration or dry AMD. Polymorphisms in genes that regulate complement activation and cholesterol metabolism are strongly associated with AMD, but the biology underlying disease-associated variants is not well understood. Here, we highlight recent studies that have used molecular, biochemical, and live-cell imaging methods to elucidate mechanisms by which aging-associated insults conspire with AMD geneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 115 publications
0
23
0
Order By: Relevance
“…It is, however, not clear if, in STGD1-iRPE, phagolysosomal dysfunction is primarily caused by ABCA4 LOF or indirectly by ceramide accumulation, as has been suggested previously ( Kaur et al., 2018 ). In the RPE, excess ceramide alters membrane dynamics and results in aberrant endosome biogenesis, impaired autophagosome trafficking, and mitochondrial fragmentation ( Kaur et al., 2018 ; Tan et al., 2020 ). In addition, ceramide’s role in phagolysosomal maturation was shown previously ( Pathak et al., 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is, however, not clear if, in STGD1-iRPE, phagolysosomal dysfunction is primarily caused by ABCA4 LOF or indirectly by ceramide accumulation, as has been suggested previously ( Kaur et al., 2018 ). In the RPE, excess ceramide alters membrane dynamics and results in aberrant endosome biogenesis, impaired autophagosome trafficking, and mitochondrial fragmentation ( Kaur et al., 2018 ; Tan et al., 2020 ). In addition, ceramide’s role in phagolysosomal maturation was shown previously ( Pathak et al., 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…In humans, increased ceramide levels in the serum and RPE have been reported in patients with AMD but not in unaffected controls. Recent studies have suggested that bis-retinoids lead to a secondary accumula-tion of cholesterol and ceramide due to a biophysical interaction between these lipids [34].…”
Section: Dysfunction Of Proteostasis and Lipid Homeostasismentioning
confidence: 99%
“…The RPE lines the back of the retina as a layer of pigmented, post-mitotic and polygonal cells. 2 The RPE has many fundamental functions that ensure the homeostasis and functioning of the retina, including: phagocytosis of shed photoreceptor outer segments, secretion of proteins for paracrine cellular communication, active transport of biomolecules, ion homeostasis, isomerization of all-transretinol to 11-cis retinal, and light absorption in melanosomes. Although not sensory cells themselves, the RPE cells are involved in intimate bioprocessing with photoreceptors, providing a critical role in their structural and functional viability.…”
Section: The Retinal Pigment Epitheliummentioning
confidence: 99%